INTEGRITAS SEBAGAI FONDASI KEPEMIMPINAN KRISTEN DI TENGAH KRISIS MORAL MASYARAKAT MODERN - Serlita Rangga; Mirna Anggela Bulawan; Yuliana Nova; Perawati Sombo Makamban; Rita (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The moral crisis facing modern society is characterized by a rise in various forms of ethical misconduct such as corruption, abuse of power, and individualism alongside a declining commitment to values ​​of truth. This situation demands leadership that is not only competent but also possesses strong integrity. This article aims to analyze integrity as the foundation of Christian leadership in the face of modern society's moral crisis. A qualitative research method was employed, utilizing a literature review approach that examined various books, scholarly articles, and relevant sources. The findings indicate that integrity is a fundamental element of Christian leadership, reflecting alignment between faith, character, words, and actions. Integrity plays a vital role in establishing credibility, setting an example, and fostering trust within both ministry and social life. Furthermore, integrity can be sustained through a healthy spiritual life, self-discipline, accountability, humility, and wisdom. Thus, integrity serves as the cornerstone of effective, credible, and transformative Christian leadership amidst the moral challenges of modern society.